Topical issues of Pedagogy of Theatrical Art - Umarov M.B (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article is devoted to the problems of proper upbringing of the sense of imitation, stamp and creativity, which is a topical issue of three scholars - Plato, Aristotle and Stanislavsky theatrical art yesterday and today. In the article, Plato's views on the art of performance and its evaluation in the book "Laws", Aristotle's views on the ability of people to imitate poetics in the work "Poetics" were compared with Stanislavsky's views on the pedagogical issues of theatrical art